Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian Makroni Imeisnack di Kecamatan Parungponteng Kabupaten Tasikmalaya - Nisa Nurlatipah; Yusni Nuryani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Purchase decisions are an important factor in determining business success. In facing increasingly intense competition, ImeiSnack Macaroni MSMEs need to pay attention to product quality and promotion to attract consumers. Good product quality can increase consumer satisfaction, while effective promotion can encourage consumers to make purchases. Therefore, product quality and promotion are assumed to influence consumer purchase decisions. This study aims to determine the influence of product quality and promotion on the purchase decision of ImeiSnack Macaroni in Parungponteng District, Tasikmalaya Regency. The research employed a descriptive-verificative method with a quantitative approach. Data were collected through questionnaires using a Likert scale distributed to 93 respondents selected through purposive sampling. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination, t-test, and F-test with the assistance of SPSS version 27. The results show that product quality has a significant influence on purchase decisions. Promotion also has a significant influence on purchase decisions. Simultaneously, product quality and promotion have a significant influence on the purchase decision of ImeiSnack Macaroni in Parungponteng District, Tasikmalaya Regency.